Evaluation of Clinical Studies of Patients With Dermatophyte Infections Caused by Trichophyton indotineae: Treatment Response and Resistance to Antifungal Medications - Tamer, Funda; Polat, Muhterem (Dermatology Practical & Conceptual, 2025)
Introduction: As the pandemic plateaus, post-COVID alopecia is resurfacing in India. COVID-19 remains a pivotal cause of alopecia, and the diagnosis of post-COVID alopecia aids in better treatment outcomes.Objectives: To estimate the prevalence of post-COVID alopecia and to evaluate the association between alopecia and COVID severity among other factors.Methods: A retrospective cross-sectional study was conducted among patients admitted to the COVID ward. Patients willing to participate were asked to fill in a pretested semi-structured questionnaire, and the PSS-10 (Perceived Stress Scale) was used to evaluate stress. Data were analyzed using the SPSS version 24.Results: Prevalence of COVID-19-induced hair loss was 37.8%. Age, sex, COVID severity, and higher stress were the significant factors, with p-value <0.05. Female sex, COVID severity, and high stress levels came to be significant independent predictors of hair loss. A majority of participants (46.9%) noticed hair loss within three months of contracting the disease.Conclusion: This study stands to be a pioneer project to investigate the prevalence of COVID-19-induced alopecia in India. The prevalence rate of 37.8% with a significant association with severity of COVID-19 highlights the importance of reviewing patient history to provide proper treatment and reassurance.